THE EFFICACY OF APPLYING URSODEOXYCHOLIC ACID IN FUNCTIONAL DISORDERS OF THE GALL BLADDER AND ODDI SPHINCTER IN CHILDREN - Абатуров, О.Є.; Бабич, В.Л. (World of Medicine and Biology, 2019)
The article is devoted to the problem of treatment of functional disorders of the gall bladder and sphincter of Oddi in children. It was revealed that in patients receiving ursodeoxycholic acid in complex therapy, unlike children who were not assigned to it, the manifestations of pain, dyspeptic and asthenovegetative syndromes significantly regressed (5% and 35%, 0% and 25%, 17,5% and 60%, respectively) (p